2017
DOI: 10.1038/s41598-017-07135-6
|View full text |Cite
|
Sign up to set email alerts
|

Refractory period in network models of excitable nodes: self-sustaining stable dynamics, extended scaling region and oscillatory behavior

Abstract: Networks of excitable nodes have recently attracted much attention particularly in regards to neuronal dynamics, where criticality has been argued to be a fundamental property. Refractory behavior, which limits the excitability of neurons is thought to be an important dynamical property. We therefore consider a simple model of excitable nodes which is known to exhibit a transition to instability at a critical point (λ = 1), and introduce refractory period into its dynamics. We use mean-field analytical calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 50 publications
3
34
0
Order By: Relevance
“…However, in some recent studies, it has been indicated that the brain is maintained near a synchronization transition (Poil et al, 2012; Gautam et al, 2015; di Santo et al, 2018; Dalla Porta and Copelli, 2019; Fontenele et al, 2019). We note that some authors have also argued for the existence of the extended critical region similar to that of “Griffiths phase” (Munoz et al, 2010; Moretti and Munoz, 2013; Odor et al, 2015; Moosavi et al, 2017). However, such critical regions also typically occur near the absorbing phase transition where the system transitions from an inactive phase to an active phase.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, in some recent studies, it has been indicated that the brain is maintained near a synchronization transition (Poil et al, 2012; Gautam et al, 2015; di Santo et al, 2018; Dalla Porta and Copelli, 2019; Fontenele et al, 2019). We note that some authors have also argued for the existence of the extended critical region similar to that of “Griffiths phase” (Munoz et al, 2010; Moretti and Munoz, 2013; Odor et al, 2015; Moosavi et al, 2017). However, such critical regions also typically occur near the absorbing phase transition where the system transitions from an inactive phase to an active phase.…”
Section: Introductionsupporting
confidence: 54%
“…Therefore, one expects b ( M ) < 1 to generally indicate subcritical behavior, while b ( M ) > 1 to indicate supercritical behavior. In fact, b ( M ) has been used to ascertain criticality in a wide range of systems including sandpile models of SOC or solar flares (Martin et al, 2010) as well as neural networks (Larremore et al, 2014; Moosavi and Montakhab, 2014; Moosavi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we will focus on the order of the emerging phase transition for various network structures and different synaptic interactions. It is believed that normal brain activity requires it to be close to a phase boundary (a critical point) which consequently provide access to both synchronous and asynchronous oscillations with small change in the input (Beggs and Timme, 2012 ; Hesse and Gross, 2014 ; Moosavi et al, 2017 ). Hence, it is important to know whether the emerging synchronization transition is continuous or abrupt.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, a wide spectrum of network-based cellular automata models, which typically constitute randomly-connected simple excitable units with nonlinear interaction, has been elaborated for large-scale numerical and/or analytically-tractable studies of critical collective behavior via avalanches, emergent synchronization and global oscillations of neuronal activity [3537,53] (some earlier ndings were reviewed in [54]). In addition to the foregoing models, some relevant models, where interference between the absolute refractory period and stochastic event occurrence may be essential, are the two-state unit model [55], the threestate unit model [5658] (see also [59,60]), the DeVille-Peskin multi-state model [61], the cortical branching model [62], and others [6365].…”
Section: Discussionmentioning
confidence: 99%